1988
DOI: 10.1093/infdis/158.1.13
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Tobramycin Dosage Regimens on Nephrotoxicity, Ototoxicity, and Antibacterial Efficacy in a Rat Model of Subcutaneous Abscess

Abstract: The influence of dosage regimen on the nephrotoxicity, ototoxicity, and antibacterial efficacy of tobramycin was assessed in Fisher rats with Pseudomonas aeruginosa subcutaneous abscesses. A subcutaneous tobramycin dose of 10 mg/kg every 4 h resulted in peak and trough serum concentrations that approximated those currently recommended for patients. Subsequently, the influence of this subcutaneous dosage regimen was compared with three other regimens that administered the same total daily dose: 20 mg every 8 h,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
33
0

Year Published

1990
1990
2006
2006

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(34 citation statements)
references
References 29 publications
1
33
0
Order By: Relevance
“…These doses could double or quadruple the amount of drug, increasing toxicity without a parallel benefit from increased antibacterial activity. Increasingly, experience and opinion indicate that severe oto-and nephrotoxicities are primarily caused by duration of treatment with a persistent drug level and not by brief periods of high drug levels (3,8,31,32,36). Transient levels of amikacin and tobramycin higher than 300 and 40 ,ug/ml, respectively, in patients caused no evidence of neuromuscular blockade, nephrotoxicity, or ototoxicity (15,31).…”
Section: Discussionmentioning
confidence: 99%
“…These doses could double or quadruple the amount of drug, increasing toxicity without a parallel benefit from increased antibacterial activity. Increasingly, experience and opinion indicate that severe oto-and nephrotoxicities are primarily caused by duration of treatment with a persistent drug level and not by brief periods of high drug levels (3,8,31,32,36). Transient levels of amikacin and tobramycin higher than 300 and 40 ,ug/ml, respectively, in patients caused no evidence of neuromuscular blockade, nephrotoxicity, or ototoxicity (15,31).…”
Section: Discussionmentioning
confidence: 99%
“…It9s pharmacodynamic and pharmacokinetic properties, however, suggest that once-daily (o.d.) administration would be more effective and less toxic; bactericidal effects depend on peak drug concentration achieved [1], toxicity is related to the amount of drug that accumulates in susceptible end organs [2] and saturation of binding sites during o.d. administration may reduce tissue accumulation [3].…”
mentioning
confidence: 99%
“…However, their auditory and renal toxicities have also been well established (9,17). Animal studies have demonstrated that nephrotoxicity was lower when the daily dose was given in a single administration compared with multiple injections (2,22). A study in humans showed that once-daily dosing decreased renal accumulation of gentamicin and netilmicin (NT) (21).…”
mentioning
confidence: 99%